1992
DOI: 10.1212/wnl.42.9.1676
|View full text |Cite
|
Sign up to set email alerts
|

The Consortium to Establish a Registry for Alzheimer's Disease (CERAD). Part III. Reliability of a standardized MRI evaluation of Alzheimer's disease

Abstract: The Consortium to Establish a Registry for Alzheimer's Disease (CERAD) has developed procedures for standardized imaging and reporting of magnetic resonance (MR) findings in Alzheimer's disease (AD) for use by neuroradiologists in multiple medical centers using a variety of MR equipment and field strengths. After initial pretesting, we revised the protocol, expanded the summary rating scale to seven points, and added more illustrations. Fourteen participating neuroradiologists evaluated 28 MR scans of elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…Accordingly, while the protocol is available it has not been recommended for use in multicenter studies, although use at any one site may be satisfactory. 18 More sophisticated means of evaluating neuroimages have since been developed, which should produce improved agreement across sites. Nevertheless, use in one study of 20 CERAD patients with neuropathologically ascertained definite AD, found a …”
Section: Neuroimaging Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, while the protocol is available it has not been recommended for use in multicenter studies, although use at any one site may be satisfactory. 18 More sophisticated means of evaluating neuroimages have since been developed, which should produce improved agreement across sites. Nevertheless, use in one study of 20 CERAD patients with neuropathologically ascertained definite AD, found a …”
Section: Neuroimaging Assessmentmentioning
confidence: 99%
“…Accordingly, while the protocol is available it has not been recommended for use in multicenter studies, although use at any one site may be satisfactory. 18 More sophisticated means of evaluating neuroimages have since been developed, which should produce improved agreement across sites. Nevertheless, use in one study of 20 CERAD patients with neuropathologically ascertained definite AD, found a significant correlation between neuroimaging evidence of temporal horn enlargement, and autopsy-identified hippocampal atrophy, as well as between severity of cerebral atrophy determined by neuroimaging and MMSE score closest in time to the scan.…”
Section: Neuroimaging Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not allow accurate information about the location or volume of the WMHs, and thus may ignore some subtle WMH differences across groups. Also different visual rating scales make it difficult to compare or reproduce the findings on WMHs across centers (Davis, et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Premortem diagnosis of AD is only probable and is based on in vivo imaging of the brain with magnetic resonance imaging or functional positron emission tomography, along with tests of cognitive and psychological function [20][21][22]. Alzheimer's disease can only be diagnosed definitively by identifying extracellular amyloid plaques composed of amyloid-β (Aβ) and neurofibrillary tangles, which consist of tau proteins, in postmortem central nervous system tissue [5,[23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%